The Effect of Innovation and Service Quality on Competitive Advantage With Dynamic Capability as a Moderating Variable (Empirical Study at BPS-Statistics Across Jawa Tengah Province) - Purnamasari, Indah; Widjajanti, Kesi; -, Indarto; xueyun, Zhong (JURNAL STUDI MANAJEMEN ORGANISASI, 2025)
This study analyzes the influence of innovation and service quality on competitive advantage with dynamic capabilities as a moderating variable at the BPS-Statistics throughout Jawa Tengah Province. Using a quantitative approach with Partial Least Square (PLS) techniques, the study involved all BPS work units in Jawa Tengah to explore the dynamics of competitive advantage in the public sector. A theoretical framework was built based on Resource-Based Theory and Dynamic Capabilities Theory to understand how organizational resources contribute to competitive value creation. The results show that innovation has a significant positive effect on competitive advantage, manifested through web-based data services, interactive statistical dashboards, and the integration of national digital platforms. Service quality is also proven to have a significant positive effect on competitive advantage, manifested through response speed, data accuracy, ease of access, and responsiveness to user needs. Dynamic capabilities show a significant positive direct effect on competitive advantage, but do not act as a moderator in the innovation-competitive advantage or service quality-competitive advantage relationship, classifying it as a quasi-moderator. These findings reveal the unique characteristics of public bureaucracy where innovation is top-down and service quality is standardized through national SOPs, limiting the adaptive flexibility of work units. The research provides theoretical contributions in understanding the application of dynamic capability theory in the public sector and practical implications for optimizing the competitive advantage of national statistical institutions through strengthening operational autonomy and contextual innovation design.